2010
DOI: 10.4054/demres.2010.22.19
|View full text |Cite
|
Sign up to set email alerts
|

Women´s wages and childbearing decisions: Evidence from Italy

Abstract: During the early 1990s, Italy became one of the first countries to reach lowest-low fertility. This was also a period in which women's education and labour force participation increased. We analyze the role of women's (potential) wages on their fertility decisions by making use of two different surveys. This enables us to apply discrete-time duration models. For first births, we find evidence of non-proportional hazards and of some "recuperation" effects; for second and third births, instead, wage exhibits sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 37 publications
1
19
1
1
Order By: Relevance
“…Using survey data for Norway and Finland, Rønsen (2004) found, however, a negative role of female wages in fertility. For Italy, Rondinelli et al (2010) used survey data and reported some negative effects of female earnings on first-birth fertility in the Italian context, but hardly any effects on higher-order childbearing; this finding is supported by a related study on first births in Italy by Vignoli et al (2012). However, Santarelli (2011) finds that Italian women's level of earnings is not associated with their first-birth rates.…”
Section: Fertility Dynamics In Germany and Denmarksupporting
confidence: 50%
See 1 more Smart Citation
“…Using survey data for Norway and Finland, Rønsen (2004) found, however, a negative role of female wages in fertility. For Italy, Rondinelli et al (2010) used survey data and reported some negative effects of female earnings on first-birth fertility in the Italian context, but hardly any effects on higher-order childbearing; this finding is supported by a related study on first births in Italy by Vignoli et al (2012). However, Santarelli (2011) finds that Italian women's level of earnings is not associated with their first-birth rates.…”
Section: Fertility Dynamics In Germany and Denmarksupporting
confidence: 50%
“…This largely stems from different operationalizations of earnings, depending on the researcher's discipline. While sociological and demographic studies regularly focus on the role of current earnings in childbearing behaviour, economists prefer to use predicted wages as input in their fertility models (e.g., Rondinelli et al 2010;Rønsen 2004). Differences in operationalization stem from differences in theoretical approaches.…”
Section: Fertility Dynamics In Germany and Denmarkmentioning
confidence: 99%
“…Many studies show that the scarce availability of affordable child care services, the rigidity of the labour market, and the limited number of part-time jobs lead to a negative relation between female labour market participation and fertility in Italy at the individual level (see e.g., Del Boca, Pasqua, and Pronzato 2005;Rondinelli, Aassve, and Billari 2010). Such a result might also be the indicator of traditional gender roles within the couple.…”
Section: The Economic Situation Of Young People In Italy: An Overviewmentioning
confidence: 99%
“…The link between economic resources and fertility is complex, since it embraces several key dimensions of the lives of individuals and societies (Baizan 2007). Although there have been many studies on the relation between female labour market participation and fertility in Italy (see, e.g., Del Boca 2002;Ongaro and Salvini 2003;Vignoli and Salvini 2008;Salvini, Pasqual, and Vignoli 2009), to date there has been little investigation of the association of fertility with income (see, e.g., Giraldo, Mazzuco, and Michielin 2004;Rondinelli, Aassve, and Billari 2010;Santarelli 2010) and with job stability (Bernardi and Nazio 2001;Salvini and Ferro 2007). This is mostly due to a lack of suitable data for empirical analyses.…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike a lot of attention to this issue, progression to develop a clear understanding of what encourages people to have a child, and processes, concerns during which decisions can be made on fertility are varying at best [17]. Furthermore, childbearing decision making is a complex multilayered process influenced by many factors [18]. In addition, human reproduction has an uncertain process and is not completely a reasonable behavior [19] and the consequence of this decision is unpredictable at least at a personal level [17].…”
Section: Introductionmentioning
confidence: 99%